Growth and magnetic properties of vertically aligned epitaxial CoNi nanowires in (Sr, Ba)TiO3 with diameters in the 1.8–6 nm range. (8th November 2016) - Schuler, V; Milano, J; Coati, A; Vlad, A; Sauvage-Simkin, M; Garreau, Y; Demaille, D; Hidki, S; Novikova, A; Fonda, E; Zheng, Y; Vidal, F
Abstract: The growth by pulsed laser deposition of fully epitaxial nanocomposites made of Co x Ni1– x nanowires (NW) vertically self-assembled in Sr0.5 Ba0.5 TiO3 /SrTiO3 (001) layers is reported. The diameter of the wires can be tuned in the 1.8–6 nm range. The composition of the wires can be controlled, with the growth sequence and the fcc crystallographic structure of the wires preserved for Co content up to 78%. The nanocomposite systems obtained display a uniaxial magnetic anisotropy with out-of-plane easy axis as shown through analysis of ferromagnetic resonance measurements. It is shown that the magnitude of the magnetic anisotropy depends sensitively on the structural quality of the nanocomposites.The energy barrier for magnetization reversal scales as the square of the diameter of the NW and reaches 60 k B T amb for 6 nm diameter, with T amb = 300 K.